The effect of the exchange rate on inflation in Syria during the period 2011-2016 Using VAR model (Damascus University Journal for the economic and Political sciences, 2021)
The study dealt with the effect of the exchange rate on inflation in Syria during the period (2011-2016). The problem of research was to answer the following question: What is the effect of the exchange rate on the rate of inflation in Syria during the period under investigation?The objective of the research is to study the relationship between the exchange rate and the inflation rate based on monthly data for the period 2011-2016 using the VAR model and the causal relationship between the two variables by Eviews (7)The research found that a change in the exchange rate by 1% leads to a change in consumer prices up by about 10% and the speed of response appear since the first month, and will in turn keep the consumer price index up by 20% - 40%The paper recommends the need to work on two axes: (i) policies that directly affect the exchange rate; and (ii) policies to reduce the rise in prices of domestic goods and services.
Keywords: exchange rate; consumer price index; inflation